POLA KOMUNIKASI KOMUNITAS I LOVE KENDARI (ILK) DALAM MEMBANGUN LOYALITAS KELOMPOK DI KOTA KENDARI - Wa Ode Rezeki Amalia (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2016)
ABSTRACT The problem in this research is the communication patterns are in use by the community I Love Kendari (ILK) in building loyalty groups and the factors that influence the loyalty of the group. This study aims to identify and explain the patterns of communication used in the community I Love Kendari (ILK) in building loyalty groups. And to find out what are the factors supporting and inhibiting factors experienced by the community group ILK in building loyalty. The results of this study expect it to provide additional knowledge and enrich the theory of community communication patterns in building loyalty groups. As well as factors supporting or inhibiting factor in building loyalty within the group. This study was performed on all members of the community ILK. It is because of this community in just a few months but already has standing members are already quite a lot. The theory used in this research is the theory analysis of the interaction process. Subjects in the study of the whole community belonging ILK since January 2015-October 2015 with the number of 150 members. By using purposive sampling technique then obtained informant as many as 10 people. The analysis technique used the qualitative descriptive. These results indicate that the pattern used by the ILK community communication patterns one-way, two-way communication pattern, and the pattern of multidirectional communication. The pattern of one-way communication and two-way tends to rarely used. The dominant communication patterns using the multidirectional communication patterns. Because it is considered more effective. Use of Communication Patterns multidirectional cause increased ILK community member loyalty. Increased loyalty of the group viewed from the comfort of community members in their communication. Thus, the use of multidirectional communication patterns make community members feel comfortable in communicating between each other in the end lead to increased member loyalty. Keywords: Communication Patterns, Loyalty